Enhanced mechanical properties and high electrical conductivity of copper alloy via dual-nanoprecipitation - Zhou, Meng; Geng, Yongfeng; Zhang, Yi; Ban, Yijie; Li, Xu; Jia, Yanlin; Liang, Shengli; Tian, Baohong; Liu, Yong; Volinsky, Alex A. (Materials characterization)
Copper alloys are widely used as lead frames, electric contact wires and pantographs due to their high electrical conductivity and excellent mechanical properties. At present work, a medium electrical conductivity and excellent mechanical properties of Cu-Co-Si-Ti-Ce alloy was obtained by the vacuum melting process with the optimum performance of 225 HV, 702.5 MPa and 40.8% IACS aging at 500 °C for 60 min via the combinations of multiple strengthening. It can be inferred that the high-volume fraction of Goss, Brass, copper and S texture was one of the main reasons for the increase of micro-hardness by comparing the texture content at different conditions. Moreover, it was observed that Co2Si and Co16Ti6Si7 phases exhibited coherent and semi-coherent interface relationships with the copper matrix, respectively, which can relieve the interfacial stress and reduce the interface energy by GPA analysis. Finally, the contributions of solid solution strengthening, work-hardening, grain boundary strengthening and precipitation strengthening were calculated, contributing most to the precipitation strengthening.